Dakwah Communication: An Alternative Way For Children Caused By Broken Home - Putra, Robby Aditya; Yusuf, Mochamad Aris; Fitri, Maulida (KOMUNIKA, 2023)
The family includes the primary shaper of this character and supporting factors in realizing these teachings through the formation of morality, as we all know that since birth, the people closest to humans are family members. This article aims to find out about da'wah communication, which is used as an alternative way for children who experience broken homes. This study uses a qualitative research method with the type of research in the form of qualitative descriptive by positioning the author as a critical instrument. As for the results in this study, that parent-child often contains views about power and authority. So it is common for children living in such families to experience rebellion. So, da'wah communication can be a solution for broken home children, based on their parents as preachers who encourage children. Because of the participation of the communicants (mad'u) of their children in the ideas or messages conveyed by the communicators (da'i), namely their parents.